2019
DOI: 10.1071/pc18058
|View full text |Cite
|
Sign up to set email alerts
|

The contest for the tall forests of south-western Australia and the discourses of advocates

Abstract: After over 50 000 years of interaction between Aboriginal people and changing climates, south-western Australia's tall forests were first logged less than 200 years ago, initiating persistent conflict. Recent conservation advocacy has resulted in the protection of 49% of these tall forests in statutory reserves, providing an opportunity to implement and benefit from a growing moral consensus on the valuing of these globally significant, tall forest ecosystems. We analysed a cross-section of literature (63 pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…These three species experience mixed‐severity fire as well: regenerating prolifically after high‐severity fire (Harvey et al., 1980; Lara et al., 1999; Person & Hallin, 1942), and surviving repeated low‐intensity fires, such as those frequent fires lit by Native Americans (Swetnam, 1993; Orville, 2008; Veblen et al., 1999). Likewise, although E. regnans forests are promoted as exemplars of infrequent, stand‐replacing fires, there is an evidence that infrequent low‐severity fires, possibly set by Indigenous Australians, may have maintained grassy understories in some of these forests prior to European invasion (Ashton, 1958, 1981), though aboriginal management of TWEF was likely much less intensive than that of drier forests (Wardell‐Johnson et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These three species experience mixed‐severity fire as well: regenerating prolifically after high‐severity fire (Harvey et al., 1980; Lara et al., 1999; Person & Hallin, 1942), and surviving repeated low‐intensity fires, such as those frequent fires lit by Native Americans (Swetnam, 1993; Orville, 2008; Veblen et al., 1999). Likewise, although E. regnans forests are promoted as exemplars of infrequent, stand‐replacing fires, there is an evidence that infrequent low‐severity fires, possibly set by Indigenous Australians, may have maintained grassy understories in some of these forests prior to European invasion (Ashton, 1958, 1981), though aboriginal management of TWEF was likely much less intensive than that of drier forests (Wardell‐Johnson et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Old growth forests and woodlands have a wide range of key ecological and ecosystem service values (Scotts 1991;Wardell-Johnson et al 2018). We sought to quantify temporal changes in the spatial extent of old growth forest and woodland in different EVCs in Victoria.…”
Section: Discussionmentioning
confidence: 99%
“…The high conservation and ecosystem service values of intact forests, including those dominated by old growth stands have long been recognised in many parts of the world (Franklin et al 1981;Scotts 1991;Bart and Forsman 1992;Spies and Franklin 1996;Van Pelt 2008;Gibson et al 2011;Watson et al 2018). This includes in Australia (Woodgate et al 1994(Woodgate et al , 1996Burgman 1996;Lindenmayer et al 2000;Wardell-Johnson et al 2018; Office of the Conservation Regulator 2019), where a range of studies have shown that, for example: (1) old growth stands are where fire severity is lowest relative to forests of younger age (Taylor et al 2014;Winoto-Lewin et al 2020);…”
Section: Introductionmentioning
confidence: 99%
“…Old growth characteristics also vary with site features such as moisture and nutrient availability: higher productivity sites generally support forests with bigger trees, more dead wood, increased heterogeneity, and higher biodiversity (Spetich et al, 1999;Chase, 2010;Hämäläinen et al, 2018). These forests often include large old trees that form keystone ecological structures which are at risk globally (Lindenmayer et al, 2012(Lindenmayer et al, , 2014Lutz et al, 2012;Wardell-Johnson et al, 2018). Big-treed ecosystems have exceptionally high value as biodiversity hubs, carbon banks, and climate refugia (Holt and Hadfield, 2007;Ashcroft, 2010;Hauer et al, 2016).…”
Section: Big-treed Old Growthmentioning
confidence: 99%